Evaluation and application of chlorine decay models for humanitarian emergency water supply contexts. Issue 21 (19th September 2022) - Wu, Hongjian; Dorea, Caetano C.
ABSTRACT: Chlorine is a widely used water disinfectant in humanitarian emergency water supply. However, its effective application can be limited by the uncertainty in initial dose determination. The target free chlorine residual in water should achieve both health objectives and aesthetic considerations, but the varying field conditions and changing source water quality may affect the performance of chlorination strategies. A chlorine dose predictive tool could assist in initial dose determination. To this end, an accurate chlorine decay kinetic model can serve as a strong foundation for developing such a tool. In this study, a literature search identified 7 basic chlorine decay kinetic models that were subsequently tested with 610 different chlorine decay test data (from a semi-systematic literature search and laboratory-generated results). The models were then ranked based on their goodness of fit ( R 2 ) and root mean square error. An empirical model, power models and parallel models were found able to fit most decay data with more than half of the regressions resulting in R 2 value over 0.97. First order models can achieve R 2 value above 0.95 when the data points in the rapid phase are excluded from the model fitting. The power models and parallel models can form a strong basis for developing a chlorine dose predictive tool if the power term and the ratio term (model parameters) can be controlled. An essential next step is to evaluate the relationships between easily obtainable water parameters in the field and the decay term in the models to allow rapid model calibration. GRAPHICAL ABSTRACT: UF0001